Understanding teenage pregnancy out of wedlock within the structure of the Malay family - Eid, Iyad Muhammad; Jalal Nori, Abdulwahed; Mohd Zin, Najibah (IIUM Press, 2022)
This paper discusses family as a risk factor in teenage pregnancy out of wedlock in the Malay community in Malaysia. Using a qualitative approach, this case study conducted in-depth semi-structured interviews with thirty Malay teenagers who experienced pregnancy outside official marriage. In the context of the current research, the girls were involved in consensual sex, which is considered illegal and strictly prohibited in Islam. The study took place in two organizations operating as rehabilitation centres to assist the girls in overcoming the traumatic experience and leading a more productive life in the future. Collected data were transcribed and analysed using the thematic analysis method. The findings showed that poor parent- daughter relationships contributed to teenage pregnancy. Parents were physically and emotionally separated from their daughters due to a demanding work schedule, argument, divorce, or neglect, and they lacked Islamic knowledge and practice; therefore, they did not treat or raise their daughters following Islamic values and principles. Funded by the Fundamental Research Grant Scheme (FRGS), this study is the first output focusing on the family as one of the factors causing teenage pregnancy.